1997
DOI: 10.1177/08959374970110021001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Oral Health in a Diverse Sample

Abstract: Measures of perceived oral health represent subjective, individual perspective of one's health. One measure commonly used is the single-item perceived oral health rating: How would you rate your overall oral health? These analyses examine the associations among age, ethnicity, and perceived oral health within the context of a comprehensive battery of 21 predisposing, enabling, and need variables. The study of compares the adult data from three United States research locations of the International Collaborative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
2
23

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 17 publications
13
115
2
23
Order By: Relevance
“…This questionnaires also include two global questions, firstly rating the health of their/their child's teeth, lips, jaws and mouth and secondly how much their/their child's teeth, lips, jaws or mouth affected their life overall. These global questions have been previously evaluated 17 and were worded: "Would you say that the health of your teeth, lips, jaws and mouth is …?" with a 5-point response format ranging from 'Excellent' to 'Poor' and "How much does the condition of your teeth, lips, jaws or mouth affect your life overall?"…”
Section: Methodsmentioning
confidence: 99%
“…This questionnaires also include two global questions, firstly rating the health of their/their child's teeth, lips, jaws and mouth and secondly how much their/their child's teeth, lips, jaws or mouth affected their life overall. These global questions have been previously evaluated 17 and were worded: "Would you say that the health of your teeth, lips, jaws and mouth is …?" with a 5-point response format ranging from 'Excellent' to 'Poor' and "How much does the condition of your teeth, lips, jaws or mouth affect your life overall?"…”
Section: Methodsmentioning
confidence: 99%
“…The absence of information on the state of the teeth present can also bring a justification, as an individual who has faced several dental problems can understand not having teeth as an effective improvement in oral health. Since individuals with some tooth loss (1-19 teeth) may have ongoing problems and be experiencing some level of pain or discomfort at the time of interview 12 . Alternatively, this discrepancy can occur because of the different references used in health self-assessment, which eventually causes weak associations between clinical status and the subject's health perception 25 .…”
Section: Discussionmentioning
confidence: 99%
“…beliefs, sociodemographic profile 11 , and oral disease history 12 . This perception is affected differently by different situations and oral diseases, such as number of teeth, use/type of prosthesis, and difficulties in chewing, considering that these relations are manifested differently between edentulous individuals and those with remaining teeth 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of only self-reported information on dental health status may have resulted in some misclassification of individuals who misrepresented their dental health status. However, the findings suggest that the perceived need for dental care may be a useful outcome measure in dentistry because of its relationship with dental utilization (17). Relative to health promotion, it has been suggested that increasing awareness and understanding regarding patient responses to perceived dental problems can assist dental health care professionals in meeting the needs of patients who remain problemoriented dental care seekers.…”
Section: Discussionmentioning
confidence: 91%